2004
DOI: 10.1002/jnr.20125
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical localization of phosphorylated protein kinase R and phosphorylated eukaryotic initiation factor‐2α in the central nervous system of SJL mice with experimental allergic encephalomyelitis

Abstract: Inflammatory cells enter the CNS and target myelin in multiple sclerosis (MS) and experimental allergic encephalomyelitis (EAE), a model of MS, and inflammation is thought to induce stress responses in the CNS. Protein kinase R (PKR) and eukaryotic initiation factor-2 alpha (eIF2 alpha) undergo phosphorylation in response to stress, and the phosphorylated forms of these proteins play a key role in regulating protein synthesis. The objective of this study was to investigate the expression profile of phospho-PKR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
19
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 57 publications
6
19
0
Order By: Relevance
“…Interestingly, the induction of ISR targeting genes such as that encoding activating transcription factor 4 (ATF4) has been demonstrated in MS lesions (47). We found modestly elevated p-eIF2α and p-PERK immunoreactivity in oligodendrocytes in the course of EAE, as previously described (35). Moreover, CNS delivery of IFN-γ before EAE onset markedly activated the PERK-eIF2α pathway in oligodendrocytes, and the protective effects of IFN-γ in EAE were dependent on the PERK pathway.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Interestingly, the induction of ISR targeting genes such as that encoding activating transcription factor 4 (ATF4) has been demonstrated in MS lesions (47). We found modestly elevated p-eIF2α and p-PERK immunoreactivity in oligodendrocytes in the course of EAE, as previously described (35). Moreover, CNS delivery of IFN-γ before EAE onset markedly activated the PERK-eIF2α pathway in oligodendrocytes, and the protective effects of IFN-γ in EAE were dependent on the PERK pathway.…”
Section: Discussionsupporting
confidence: 85%
“…To determine whether the PERK pathway is involved in the protective effects of IFN-γ in EAE-induced demyelination, we monitored the level of p-PERK and p-eIF2α in oligodendrocytes during the course of EAE. Colocalization analysis with the CC1 antibody revealed that few oligodendrocytes were p-PERK-positive and p-eIF2α-positive in the spinal cords of control mice at EAE onset, consistent with a previous report (35). In contrast, CNS delivery of IFN-γ markedly enhanced the activation of the PERK-eIF2α pathway in oligodendrocytes of IFN-γ CNS+ ;Perk +/+ mice ( IFN-γ CNS-;Perk +/+ mice at PID14 (Supplemental Figure 3).…”
Section: The Protective Effects Of Ifn-γ On Eae Are Associated With Asupporting
confidence: 92%
“…Our findings support those in other cell types for an additional role of PKR in the induction of IFNs, cytokines, and chemokines (Melchjorsen et al, 2002;Yang et al, 1995). Phosphorylated PKR or phosphorylated eIF2a have been observed in models of MS and other neurodegenerative diseases, particularly Alzheimer's disease and Huntington's disease (Chakrabarty et al, 2004;Chang et al, 2002;Peel and Bredesen, 2003;Peel et al, 2001). Astrogliosis is a common feature of these diseases (Hedreen and Folstein, 1995;Minagar et al, 2002), and whether PKR contributes to the activation of astrocytes under these conditions remains to be determined.…”
Section: Discussionsupporting
confidence: 84%
“…More recently, Chakrabarty et al (2004) showed that phospho-PKR and phospho-eIF2␣ were present in oligodendrocytes of both control and EAE animals, and the use of a semi-quantitative scoring scale revealed that the number of phospho-eIF2␣ positive oligodendrocytes was enhanced during EAE. This semiquantitative approach relied on the notion that a percentage of oligodendrocytes was unstained in control animals, due to a very low or absent expression of phospho-eIF2␣, while the number of oligodendrocytes expressing phospho-eIF2␣ increased in the stressed cells.…”
Section: Introductionmentioning
confidence: 99%